2017
DOI: 10.17219/acem/61431
|View full text |Cite
|
Sign up to set email alerts
|

IFN-γ induces senescence-like characteristics in mouse bone marrow mesenchymal stem cells

Abstract: Background. Mesenchymal stem cells (MSC) are considered promising in tissue repair and regeneration medicine due to their proliferation and differentiation ability. Many properties of MSC are affected by cytokines, and IFN-γ has been shown to regulate MSC in many aspects. Senescence affects the proliferation, differentiation and cytokine secretion of MSC.Objectives. To investigate the effects of IFN-γ on the senescence-associated properties of MSC.Material and methods. The MSC used in our study were isolated f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 24 publications
2
16
0
Order By: Relevance
“…A recent study by Yang et al claimed that IFN-γ induces senescence-like characteristics in murine MSC, which could explain our findings that MSC maintenance is impaired upon exposure to IFN-γ [ 43 ]. In contrast, Chinnadurai et al, showed that prelicensing with IFN-γ can correct some of the senescence-associated characteristics of cultured human MSC [ 44 ].…”
Section: Discussionmentioning
confidence: 77%
“…A recent study by Yang et al claimed that IFN-γ induces senescence-like characteristics in murine MSC, which could explain our findings that MSC maintenance is impaired upon exposure to IFN-γ [ 43 ]. In contrast, Chinnadurai et al, showed that prelicensing with IFN-γ can correct some of the senescence-associated characteristics of cultured human MSC [ 44 ].…”
Section: Discussionmentioning
confidence: 77%
“…Cellular senescence is activated during intrinsic stress such as extensive cell replication and/or extrinsic stress like ultraviolet radiation, oxidative damage, activated oncogenes, and chronic in ammation. In particular, during chronic in ammation that occurs with liver cirrhosis, hematopoietic stem cell-associated disorders, chronic human immunode ciency virus (HIV) infection, myelodysplastic syndromes, ulcerative colitis and LRA, immune cells produce strong oxidizing genotoxic substances that are able to induce the cellular senescence [18][19][20][21]. In the in ammation milieu, pro-in ammatory cytokines are produced from stimulated lymphocytes by antigens or pathogens and activate immune cells, inhibit proliferation of transformed cells and intensify anti-viral/-tumor effects on cells; moreover, they also induce cellular senescence in diverse kinds of cells including melanocytes, endothelial cells and MSCs [10,[21][22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, during chronic in ammation that occurs with liver cirrhosis, hematopoietic stem cell-associated disorders, chronic human immunode ciency virus (HIV) infection, myelodysplastic syndromes, ulcerative colitis and LRA, immune cells produce strong oxidizing genotoxic substances that are able to induce the cellular senescence [18][19][20][21]. In the in ammation milieu, pro-in ammatory cytokines are produced from stimulated lymphocytes by antigens or pathogens and activate immune cells, inhibit proliferation of transformed cells and intensify anti-viral/-tumor effects on cells; moreover, they also induce cellular senescence in diverse kinds of cells including melanocytes, endothelial cells and MSCs [10,[21][22][23][24][25]. Because cellular senescence is de ned as the irreversible changes that inhibit cellular division, growth, and function, senescent MSCs from an experimentally-induced model as well as RA and systemic lupus erythematosus (SLE) patients exhibit degradation of distinct cellular features, including differentiation potential, immunomodulation properties, misregulation of proin ammatory cytokine production and reduction in migratory ability [2,5,10,11,19,21,[23][24][25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…It was found that IFN-γ could induce senescence-like characteristics in mouse bone marrow mesenchymal stem cells [40]. The accumulation of IFN-γ-producing effector CD4 + T cells in the mediastinal lymph nodes contribute to myocardial aging [41]. Together, these data suggest that the progressively increased peripheral Th1 cells in the patients with autoimmune diseases facilitate their reentry into the thymus and contribute to accelerated thymic involution.…”
Section: Discussionmentioning
confidence: 99%